Effects of leg strength on heart rate response during cross country skiing race - Oz, E.; Cetin, E.; Yarim, I.; Altunsoy, M. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
XC skiing is the most physically demanding sport of all. It requires all available power of upper and lower extremity on different types of XC races at varying portions. Increasing available strength of lower extremities may positively affect the uphill performance of XC skiers.